2019
DOI: 10.3847/1538-4357/ab017b
|View full text |Cite|
|
Sign up to set email alerts
|

Revisit of Nonlinear Landau Damping for Electrostatic Instability Driven by Blazar-induced Pair Beams

Abstract: We revisit the effect of non-linear Landau (NL) damping on the electrostatic instability of blazarinduced pair beams, using a realistic pair-beam distribution. We employ a simplified 2D model in k-space to study the evolution of the electric-field spectrum and to calculate the relaxation time of the beam. We demonstrate that the 2D model is an adequate representation of the 3D physics. We find that non-linear Landau damping, once it operates efficiently, transports essentially the entire wave energy to small w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…For a full discussion of the results we refer to [25]. In the following summarize the main findings.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…For a full discussion of the results we refer to [25]. In the following summarize the main findings.…”
Section: Resultsmentioning
confidence: 91%
“…The primary goal of this paper is to investigate the effect of non-linear Landau damping considering the realistic behavior of the electrostatic growth rate at large wave numbers for blazar-induced pair beams. For a more detailed description of this research we refer to our main paper [25].…”
Section: Introductionmentioning
confidence: 99%
“…A plausible explanation of such a mystery is that virulent kinetic plasma instabilities in the IGM, induced by the pair beams, reduce the pair-beam energy on time scales much shorter than that of the inverse Compton cascade. The validity of such a scenario strongly depends on the nonlinear saturation of these instabilities (Miniati & Elyiv 2013;Chang et al 2014;Sironi & Giannios 2014;Chang et al 2016;Kempf, Kilian & Spanier 2016;Shalaby et al 2017a;Vafin et al 2018Vafin et al , 2019.…”
Section: Beam-plasma Instabilities In the Intergalactic Mediummentioning
confidence: 99%
“…Using analytical methods Vafin et al [316] found that the energy loss by driving the electrostatic instability is likely dominant, suppressing the GeV-band cascade emission. Modeling the spectral evolution of the waves under nonlinear Landau damping instead suggests that there is no constant saturation level in the resonant band in k space, which might invalidate the analytical extrapolation [317].…”
Section: Tev Pair Beamsmentioning
confidence: 99%